A(10) + B = B(10) + A - 9
A+B = 11
=================================
10A - A = 10B - B - 9
9A = 9B - 9
A = B -1
A+B = 11
(B-1)+B = 11
2B-1 = 11
2B = 12
B = 6
A+6 = 11
A=5
2007-02-07 04:39:45
·
answer #1
·
answered by Grant d 4
·
0⤊
0⤋
Let x be the first digit and y be the second digit.
Then the number is
10x + y
When the digits are reversed, y will be the first digit and x the second digit, so the number after reversing the digits will be:
10y + x.
Since the number will be 9 more than the original number,
10y + x = 10x + y + 9
9y - 9x = 9
Dividing both sides by 9,
y - x = 1
y = 1 + x ..........equation (1)
Since the sum of digits in the original number is 11,
x + y = 11
y = 11 - x ...........equation (2)
From eqn. 1 and 2
1 + x = 11 - x
2x = 10
x = 5
Hence, y = 11 - 5 = 6
Thus the original number is
10x + y
= 10*5 + 6
= 50 + 6
= 56.
2007-02-07 12:53:16
·
answer #2
·
answered by Gopal Paudel 1
·
0⤊
0⤋
Here's a two-digit number with digits a & b: 10a + b
Reverse the digits: 10b + a
Write the two equations:
the new number is 9 more than the original number:
10b + a = 10a + b + 9
9b = 9a + 9
b = a + 1
the sum of the digits of the original number is 11:
a + b = 11
Substitute b = a + 1 into a + b = 11:
a + a + 1 = 11
a = 5
b = 6
original number is 56
2007-02-07 12:42:13
·
answer #3
·
answered by ? 4
·
0⤊
0⤋
56
Let XY be the original number. Just like 32 means 3 tens and 2 ones, we have 10X + Y for the smaller number. If we switch it, we get YX as a two digit number, or 10Y plus X. Now, it is nine more. So, our first equation is
(1) (10X + Y) + 9 = (10Y + X).
The sum of the digits is eleven, so that
(2) X + Y = 11.
That is your second equation.
2007-02-07 12:36:46
·
answer #4
·
answered by Asking&Receiving 3
·
0⤊
0⤋
original number is 56. reverse the digits to make 65. 65 is 9 more than 56.
5+6=11
65-56=9
2007-02-07 12:38:28
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
56.
56 reversed is 65, 65-56=9, and 5+6=11
You know that the digits had to be next to each other (because it was nine) and that they had to add up to 11.
2007-02-07 12:39:13
·
answer #6
·
answered by Julia 3
·
0⤊
0⤋
x is digit 1
y is digit 2
(y*10) + x = 9 + (x*10) + y
==> 9*y - 9*x = 9
x + y = 11
solves x=5 y=6
2007-02-07 12:43:27
·
answer #7
·
answered by ANC 2
·
0⤊
0⤋
Let T and U be the tens and units digits of the original. Then 10T+U is its value, and the value of the reverse number is 10U+T. That makes your equations
10U+T = 9 + 10T+U and
T + U = 11.
2007-02-07 12:40:34
·
answer #8
·
answered by Philo 7
·
0⤊
0⤋
y=17x+33-92
y=7
2007-02-07 12:36:21
·
answer #9
·
answered by Jessi-is-me 2
·
0⤊
4⤋